Implementation of Scrum in the manufacture of non-invasive blood sugar detection devices using PPG signals - Kanza, Rafly Arief; Febrianti, Erita Cicilia; Afifah, Izza Nur; Maulana, Rifqi Affan; Fariza, Arna; Rante, Hestiasari (International Journal of Applied Sciences and Smart Technologies, 2024)
This study presents the effective integration of Scrum methodology in the production process of non-invasive blood sugar testing devices using Photoplethysmography (PPG) signals. During three months, a team consisting of a Product Owner, Scrum Master, and Developer Team successfully utilized Scrum's agile structure to manage the challenges of PPG signal processing, hardware integration, and software development. The repeated sprint cycles enabled swift adjustment to new obstacles and stakeholder input, guaranteeing both effectiveness and agility in the development process. The dynamic approach facilitated both the punctual delivery of complex medical equipment and the cultivation of a culture focused on ongoing enhancement, establishing a model for the future use of agile approaches in healthcare technology. The successful implementation highlights the effectiveness of Scrum in managing the complexities of medical device development. It provides a model for improving non-invasive blood sugar detection devices and establishes agile methodologies as a key driver of innovation in healthcare technology.